Identity struggle in Turkey from the era of Kemal Ataturk to Recep Tayyip Erdogan - Kajour, Antar (International Journal of Psychosocial Rehabilitation, 2022)
Modern Turkey has adopted secularism and extreme nationalism as modes of governance and life, resulting in a direct and prolonged conflict with the Turkish people, which has harmed Turkey’s progress and prosperity. Adnan Menderes, Togrot Ozal, and Necmettin Erbakan attempted to bring the state closer to the people by granting more freedoms and respect for human rights, and they were mostly successful. However, they were unable to cross the red lines drawn by extremist secularism, which has severely harmed Turkey’s freedoms and human rights. With the election of Recep Tayyip Erdogan, he attempted to remove the constraints that continued to oppress the Turkish people, and he strengthened democracy, freedoms, and human rights, allowing the Turkish people complete religious and cultural freedom. And Erdogan’s strategy in this regard is as follows: 1- Reviving the Turkish people’s religious spirit. 2- Changing the law to strengthen democracy. 3- Bringing back the concept of secularism. 4- Case studies and financial success